The important of information & communications technology in Uber services - Lim, Cheh Er; Tan, Kai Li; Chin, Mei Jing; A. Jalil, Emy Ezura (2017)
There is a growing interest and concern towards the concept of sustainable transport due to the low functionality of public transport, unregulated taxi pricing, lack of parking space, insufficient availability of taxies and the growing number of traffic congestion during peak hour in urban and sub-urban area.Uber services appear to be cost effective and a sustainable way to travel for public user especially commuter.The study aimed to explore the relationship between information & communications technology (ICT) and the effectiveness of Uber services.The factor that had been found that influence public ridership is information & communications technology.The application of convenience sampling with the usable data from 408 respondents who at least has the intention to use for future ride has been conducted by using online survey.In this study, there is a significant relationship between monthly salary & occupation with information & communications technology.This study contributed to city planner and local planner in developing or planning in order to have a smart city.